Did surgical failure and complications affect incontinence-related quality of life in women after transobturator sling procedure? - Wen-Chu Huang; Hui-Hsuan Lau; Tsung-Hsien Su (Elsevier, 2018)
Objective: To report the objective outcome, subjective measurement of incontinence-related quality of life (QoL) for female urodynamic stress incontinence (USI) after transobturator sling surgery (TVT-O) and to evaluate the effects of surgical failure and complications on QoL. Materials and methods: We analyzed the data from women who underwent TVT-O for USI and completed two validated QoL questionnaires, the Urogenital Distress Inventory (UDI-6) and Incontinence Impact Questionnaire (IIQ-7) preoperatively and at least 12 months postoperatively. We evaluated the subjective results of QoL questionnaires, objective results and compare the effect of QoL on those with surgical failure and complications after TVT-O surgery. Results: A total of 78 women were followed for a median of 13.5 months (range 12-15 months) after surgery. Within this group, 75 (96%) were considered subjectively cured or improved after TVT-O. There were significant improvements in the IIQ-7 and total UDI-6 scores postoperatively, as well as in the UDI-6 subscales for urge, stress and voiding dysfunction symptoms. Even the 18 women with objective urodynamic failure had significant improvement in QoL scores. For those with surgical related complications, the QoL scores were also significantly improved. Conclusions: TVT-O for USI resulted in improvement of incontinence-related QoL including urgency, stress, and voiding dysfunction symptoms. Surgical failure and complications didn't impair postoperative QoL. Keywords: Complication, Quality of life, Stress urinary incontinence, Transobturator tape, Urodynamic stress incontinence